Farmers’ strategies as building block for rethinking sustainable intensification - Suhardiman, Diana; Giordano, Mark; Leebouapao, L.; Keovilignavong, Oulavanh (Springer, 2016)
Agricultural intensification, now commonly referred to as sustainable intensification, is presented in development discourse as a key means to simultaneously improve food security and reduce rural poverty without harming the environment. Taking a village in Laos as a case study, we show how government agencies and farmers could perceive the idea of agricultural intensification differently. The study illustrates how farmers with the opportunities for groundwater use typically choose to grow vegetables and high valued cash crops rather than intensify rice production. This contrasts with government and donor supported efforts to promote rice intensification as a means to increase food security and reduce rural poverty. The article’s main message is that farmers’ differing strategies are related to a variety of household characteristics and that farmers’ strategies should be central to the current discussion on sustainable intensification.